Perlakuan Akuntansi Karbon di Indonesia - Monika Meliana Taurisianti; Elisabeth Penti Kurniawati (Jurnal Ekonomi dan Bisnis, 2014)
This research aims to understand the implementation of accounting for carbon, about how it can be measured, recognized, recorded, presentedand disclosed based on Pernyataan Standar Akuntansi (PSAK) 19, 23, 32 and 57, also the impact toward the financial ratios. The object of this study is the financial statements of an integrated timber company in Indonesia. This study has analyzed the enables account to be used to record accounting for carbon, also analyzed the impact of implementation of accounting for carbon toward the financial ratios. The results of this study are support the previous study, which intangible asset can be recognized based on PSAK 19, whereas asset and contingent liabilities can be recognized based on PSAK 57. This study also fit out the previous study, which a company can recognize its expense and other income based on PSAK 19, 23 and 32 as a basis for forestry accounting in Indonesia.